Mot framtiden på gamla spår? : Regionala intressegrupper och beslutsprocesser kring kustjärnvägarna i Norrland under 1900-talet - Andersson, Fredrik (Umeå universitet, Institutionen för ekonomisk historia, 2004)
In this dissertation the construction of two coastal railways, the East Coast Line and the Bothnia Line, in the Norrland region of northern Sweden is used as a case study of how regionally based interest groups are formed, and how they gain access to decision-making processes on a national level. In periods when a number of preconditions were in place, a window of opportunity opened for the coastal railway that the regional elites could exploit. Among these was the ability to form a coherent regional interest group, through institutions that created platforms and power-bases that enable regional elites to co-operate and act on regional and national levels.The existence of an institutional framework that was adapitve towards regional railway promotion was also important. The study shows that the coastal railway had a very flexible role on the agenda, as it provided a fixed solution against which actors could pin a multitude of different problems. An important factor for explaining the development of the coastal railway question in Norrland was the ideological notion of the region itself. Being a vast, resource-rich and sparsely populated region, Norrland had almost always received special consideration in both public opinion and national policy making. It also created a remarkable stubbornness among the regional actors in working for the coastal railway. Regional interest groups had also learnt that linking their claims to Norrland's peripheral position had high legitimacy on the national arena, by claiming the need for regional fairness and/or the national importance of the regional export-intensive industries. This was instrumental in justifying the repeated exemptions from the national railway policy regimes that ultimately were decissive in making the regional elites successful.